An Analysis of Activity Preferences and Motivation for Outdoor Recreation - Vanessa Gaffar; Yeni Yuniawati; Oce Ridwanudin (Penerbit STKIP PGRI Bangkalan, 2026)
Hiking is one of the popular sport tourism activities in Indonesia, especially in West Java Province. It’s not only favored by professionals but also amateurs who are eager to spend their leisure time outdoors. These participants do the activity based on various motivations and preferences. Activity preferences are activities chosen by sport tourism participants and can be used as a basis for conducting market segmentation. This study aimed to investigate dominant factors of participants’ outdoor recreation motivation and its influence on outdoor activity preferences. Quantitative research was used in this study. Data were collected from 411 respondents who hiked Ciremai Mountain and Papandayan Mountain in West Java Province. Data were analysed using Confirmatory Factor Analysis (CFA) and Structural Equation Model (SEM). Results showed that achievement, learning and sociality, independent and personal development, and relaxation formed outdoor activity motivation. The most dominant factor was learning and sociality, while the least dominant was relaxation. Motivation was also proven to have a significant influence on activity preference. Most of the hikers were willing to explore and learn new things when they hiked, which can be an opportunity for the management to socialize sustainable behaviour aspects around the area.